2022
DOI: 10.3390/bs12090324
|View full text |Cite
|
Sign up to set email alerts
|

Eliciting Learner Knowledge: Enabling Focused Practice through an Open-Source Online Tool

Abstract: Eliciting and interpreting students’ ideas are essential skills in teaching, yet pre-service teachers (PSTs) rarely have adequate opportunities to develop these skills. In this study, we examine PSTs’ patterns of discourse and perceived learning through engaging in an interactive digital simulation called Eliciting Learner Knowledge (ELK). ELK is a seven-minute, chat-based virtual role play between a PST playing a “teacher” and a PST playing a “student” where the goal is for the teacher to find out what the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…Given the current vision for science teaching and learning emphasizes students developing their own understanding of scientific phenomena by engaging in collaborate sense‐making discussions, such as argumentation, there is a greater need for teacher education programs to prepare PSTs to implement this high leverage and ambitious teaching practice in the classroom (Berland & Reiser, 2009; NRC, 2012). To support PSTs in learning how to facilitate argumentation‐focused discussions, researchers have explored the use of online simulated teaching experiences and found that this form of approximation of practice does give PSTs the opportunity to engage in this form of discourse in a less complex environment (Levin et al, 2019; Mikeska et al, 2023, Thompson et al, 2022). While previous research shows that elementary PSTs can be responsive to students' ideas (Estapa & Davis, 2023; Levin et al, 2009), it is unclear how they are responding to students' ideas while facilitating an argumentation‐focused discussion (Mikeska et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the current vision for science teaching and learning emphasizes students developing their own understanding of scientific phenomena by engaging in collaborate sense‐making discussions, such as argumentation, there is a greater need for teacher education programs to prepare PSTs to implement this high leverage and ambitious teaching practice in the classroom (Berland & Reiser, 2009; NRC, 2012). To support PSTs in learning how to facilitate argumentation‐focused discussions, researchers have explored the use of online simulated teaching experiences and found that this form of approximation of practice does give PSTs the opportunity to engage in this form of discourse in a less complex environment (Levin et al, 2019; Mikeska et al, 2023, Thompson et al, 2022). While previous research shows that elementary PSTs can be responsive to students' ideas (Estapa & Davis, 2023; Levin et al, 2009), it is unclear how they are responding to students' ideas while facilitating an argumentation‐focused discussion (Mikeska et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The ELK online simulated environment involves pairs of PSTs engaging in a 7‐min typed chat on the online Teacher Moments platform (Thompson et al, 2022; Wang et al, 2021). Although this online simulated environment requires one PST to play the role of a teacher and the other to play the role of a student, the ELK platform provides each PST with specific information pertinent to their role before starting the chat.…”
Section: Online Simulated Learning Experiencesmentioning
confidence: 99%
See 1 more Smart Citation